An SKP-ABE Scheme for Secure and Efficient Data Sharing in Cloud Environments. (17th June 2022) - Hwang, Yong-Woon; Kim, Su-Hyun; Seo, Daehee; Lee, Im-Yeong
Abstract : Security threats such as data forgery and leakage may occur when sharing data in cloud environments. Therefore, it is important to encrypt your data and securely access it when sharing it with other users via a cloud server. Of the various security technologies, research on secure data sharing commonly employs Key Policy Attribute-Based Encryption (KP-ABE). However, existing KP-ABE schemes generally lack ciphertext search features. Furthermore, even if a KP-ABE scheme incorporates it, the number of searches required increases markedly by the number of attributes used in the search. It in turn proportionally increases the ciphertext size. In addition, the attribute authority (AA) could be attacked, which can result in the leakage of users' decryption keys. AA is a server that manages user attributes and decryption keys when using attribute-based encryption in a cloud environment. If the AA is curious, it can cause problems with the key escrow with the attributes and decryption (secret) key information of the users it knows. In this paper, to solve all these problems, we present a new scheme called Searchable Key-Policy Attribute-Based Encryption (SKP-ABE) for secure and efficient data sharing in the cloud. This proposed SKP-ABE scheme allows fast ciphertext search and keeps the ciphertext of constant size. The key escrow problem is solved via user key generation.